2009
DOI: 10.1007/s11252-009-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the non-native flora of Ensenada, a fast growing city in northwestern Baja California

Abstract: Urbanized areas show a high proportion of non-native plants and can work as dispersal points to the surrounding areas. Ensenada is a fast growing city located in the northwestern peninsula of Baja California (Mexico). It is the southern extreme of a binational, coastal urban corridor that extends from Los Angeles, California south to Ensenada. This corridor is part of the biodiversity hotspot of the California Floristic Province. The aim of this study was to analyze the composition and distribution of the spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…The NCEAS database contains only a few cities from Africa, Latin America and the Caribbean, and Southeast Asia and the Pacifi c Islands. The Garcillán et al ( 2009 ) study of Ensenada, Mexico provides insights into patterns of plant diversity in Central America. They report that 61 % of the vascular plant species found in arroyo (dried river beds) and vacant lot habitats are non-native species.…”
Section: Biological Hotspots and Urban Landscapesmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCEAS database contains only a few cities from Africa, Latin America and the Caribbean, and Southeast Asia and the Pacifi c Islands. The Garcillán et al ( 2009 ) study of Ensenada, Mexico provides insights into patterns of plant diversity in Central America. They report that 61 % of the vascular plant species found in arroyo (dried river beds) and vacant lot habitats are non-native species.…”
Section: Biological Hotspots and Urban Landscapesmentioning
confidence: 99%
“…Ensenada has experienced rapid growth and expansion typical of cities in the global south and had a higher percentage of non-native species than reported cities in the same biogeographic realm in the United States. Garcillán et al ( 2009 ) suggest that rapid urbanization from recent population growth has resulted in a loss of remnant habitats and an associated increase in the proportion of non-native plant species. Similar changes may occur in rapidly developing cities (see Chap.…”
Section: Biological Hotspots and Urban Landscapesmentioning
confidence: 99%
“…Pyšek (1998) in a study, involving 54 central European cities, reported a high proportion of alien plant species which ranged between 20% and 60%. The proportion of alien species found in Ensenada, a fast-growing city located in the north-western peninsula of Baja California (Mexico) was also as high as 61% (Garcillán et al 2009). Kowarik (1990) also reported that Polish cities have an average of 50% to 70% alien plant species.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con Vibrans (2009), esta planta es originaria del norte de África y es bien conocida por ser una invasora de desiertos, se ha señalado que en México se comporta como una típica arvense. Garcillán et al (2009) reportaron que tiene preferencia por terrenos abandonados en la ciudad de Ensenada, Baja California. En Cal-IPC (2007), se menciona que B. tournefortii es abundante en ambas costas de Baja California; sin embargo, en el mapa de distribución potencial de esta especie su presencia no se observa en la zona costera del Golfo de California, por lo que es necesario contar con más colectas de herbario para poder tener un mejor diseño de la interpretación de la distribución potencial de esta planta, ya que sólo se encuentra en la costa del Pacífi co.…”
Section: Discussionunclassified
“…Garcillán et al (2009) registraron en zonas urbanas de la ciudad de Ensenada, B.C., 33 familias, 122 géneros y 161 especies, de las cuales 98 (61%) fueron no nativas. Mientras que Villaseñor y Espinosa-García (2004) estimaron para Baja California 219 especies exóticas.…”
Section: Importancia Del Uso De Modelos De Distribución De Especiesunclassified